Case report: Microsatellite instability determination is not always black and white in Lynch syndrome diagnosis - Rodriguez, Julieta E.; Vasseur, Damien; Bani, Mohamed Amine; Cabaret, Odile; Cotteret, Sophie; Muleris, Martine; Golbarg, Veronica; Malka, David; Pudlarz, Thomas; Caron, Olivier; Smolenschi, Cristina (Frontiers in Oncology, 2024)
Introduction: Microsatellite instability (MSI) is a genetic marker that is useful in the detection and treatment of Lynch syndrome (Sd). Although conventional techniques like immunohistochemistry and polymerase chain reaction (PCR) are standards for MSI detection, the advent of next-generation sequencing (NGS) offers new possibilities, especially with circulating DNA. Case Report: We present the case of a 26-year-old with Lynch Sd and BRAF-V600E mutated metastatic colon cancer. Discordant MSI results between conventional methods and NGS posed challenges in making treatment decisions. Subsequent NGS analysis revealed high MSI status, leading to participation in immunotherapy trial with remarkable clinical response. Conclusion: This case emphasizes the importance of comprehensive molecular profiling and strong interdisciplinary collaborations, especially in cases with ambiguous MSI results.